The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1159/000360426
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Glomerular Filtration Rate Decline as a Predictor of Dialysis in Kidney Transplant Recipients

Abstract: Background: It is now common for individuals to require dialysis following the failure of a kidney transplant. Management of complications and preparation for dialysis are suboptimal in this group. To aid planning, it is desirable to estimate the time to dialysis requirement. The rate of decline in the estimated glomerular filtration rate (eGFR) may be used to this end. Methods: This study compared the rate of eGFR decline prior to dialysis commencement between individuals with failing transplants and transpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…In these studies, the reported annual eGFR decline for the whole CKD population ranged between 1.5 and 2.1 mL/min/1.73 m 2 , and for patients who initiated dialysis, it ranged between 3.9 and 7.3 mL/min/1.73 m 2 . 15 , 17 , 18 Previous literature is in line with our finding that the mean annual rates of kidney function decline in CKD 3–5 cohorts are much lower than in dialysis-based studies.…”
Section: Discussionsupporting
confidence: 87%
“…In these studies, the reported annual eGFR decline for the whole CKD population ranged between 1.5 and 2.1 mL/min/1.73 m 2 , and for patients who initiated dialysis, it ranged between 3.9 and 7.3 mL/min/1.73 m 2 . 15 , 17 , 18 Previous literature is in line with our finding that the mean annual rates of kidney function decline in CKD 3–5 cohorts are much lower than in dialysis-based studies.…”
Section: Discussionsupporting
confidence: 87%
“…Transplant recipients may exhibit a more rapid loss of kidney function in the months prior to ESRD than the transplant-naïve CKD population [24]. This study demonstrates that the median survival time after commencing dialysis is short, and presumably, the window of opportunity for transplantation is shorter again; this, combined with the rapidity of decline in graft function prior to transplant failure, necessitates a degree of urgency in the management of these recipients.…”
Section: Discussionmentioning
confidence: 99%
“…3 Additionally, several studies have found that repeated measurements of allograft function can add value when predicting clinical outcomes. 4,5 Hence, capturing a comprehensive set of risk factors for allograft failure requires not only large, well annotated, deeply phenotyped cohorts 6 of kidney transplant recipients but also a dynamic and integrative method that uses repeated and diverse measures recorded throughout patient follow-up.…”
Section: Introductionmentioning
confidence: 99%